Development of recombinase polymerase amplification combined with a lateral flow dipstick assay for rapid and simple detection of Tylenchulus semipenetrans in soil - Song, Zhiqiang; Cheng, Yi; Wang, Tuhong; Wang, Qipei; Qiu, Caisheng; Qiu, Huajiao (Pest management science, 2025)
BACKGROUND Tylenchulus semipenetrans, the causal agent of citrus slow decline disease, is one of the most destructive plant‐parasitic nematodes in all citrus‐growing regions of the world, causing significant reductions in citrus growth and yield. Accurate and rapid detection of T. semipenetrans is critical for the diagnosis and effective control of the disease. RESULTS We developed a rapid, visual, isothermal detection method using recombinase polymerase amplification combined with a lateral flow dipstick (RPA‐LFD) assay to detect T. semipenetrans in soil. The primers and a probe were designed based on sequence differences in the internal transcribed spacer region 1 (ITS1) of ribosomal DNA (rDNA) among T. semipenetrans and four other Tylenchulus species. The RPA reaction can be performed in 10–25 min at a constant temperature ranging from 30 to 45 °C, and the result can be read directly on the LFD within 3 min. Under the optimized conditions, the RPA‐LFD assay could specifically detect T. semipenetrans with a sensitivity as low as 10−2 second‐stage juveniles/0.5 g soil, which was 10‐fold more sensitive than that of the conventional PCR assay. Furthermore, we combined a soil DNA extraction method with the RPA‐LFD assay to achieve simple and rapid detection of T. semipenetrans in natural field soil samples within 1 h. CONCLUSION The developed RPA‐LFD assay is a simple, rapid, specific, sensitive and visual method for detecting T. semipenetrans. It shows great potential for on‐site rapid detection applications, especially in resource‐limited settings. © 2025 Society of Chemical Industry. A rapid and simple detection method based on recombinase polymerase amplification combined with a lateral flow dipstick (RPA‐LFD) assay was developed for the detection of Tylenchulus semipenetrans in soil. This method shows great potential for on‐site rapid detection applications, especially in resource‐limited settings.